1999
DOI: 10.1037/0893-3200.13.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and the spiritual realm: The role of proximal and distal religious constructs in marital functioning.

Abstract: Ninety-seven couples completed questionnaires about their involvement in joint religious activities and their perceptions regarding the sanctification of marriage, including perceived sacred qualities of marriage and beliefs about the manifestation of God in marriage. In contrast to individual religiousness and religious homogamy (distal religious constructs), these proximal religious variables directly reflect an integration of religion and marriage, and they were associated with greater global marital adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
378
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(407 citation statements)
references
References 50 publications
(88 reference statements)
21
378
1
3
Order By: Relevance
“…Coefficients are standardized regression coefficients. ‫ء‬ p Ͻ .05. endowed with a spiritual or religious importance) generate more goal striving (e.g., Mahoney, Carels, et al, 2005;Mahoney et al, 1999) and less goal conflict (Emmons, Cheung, & Tehrani, 1998). Third, the evidence for the proposition that religiousness promotes self-monitoring is mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Coefficients are standardized regression coefficients. ‫ء‬ p Ͻ .05. endowed with a spiritual or religious importance) generate more goal striving (e.g., Mahoney, Carels, et al, 2005;Mahoney et al, 1999) and less goal conflict (Emmons, Cheung, & Tehrani, 1998). Third, the evidence for the proposition that religiousness promotes self-monitoring is mixed.…”
Section: Discussionmentioning
confidence: 99%
“…strong marriages [34,35]. Quantitative studies have also reported that couples who perceived their marriage as "sacred" experienced lower levels of marital conflict and higher overall levels of marital satisfaction [22]. Indeed, Burr and colleagues posited in their recent volume, Sacred Matters, that viewing any aspect of life as "sacred" endows it with unique power and force, but that this may be especially true with marriage and family relationships, as Mahoney has documented [1].…”
Section: Spiritual Beliefs and Marriagementioning
confidence: 99%
“…Mahoney et al found that couples who pray for each other and attend religious services together seem to experience better marital quality [22]. Shared religious practice also appears to help couples with preventing and resolving marital conflict [23].…”
Section: Religious Practices and Marriagementioning
confidence: 99%
“…Spiritual strivings were also rated as more important, requiring more effort, and engaged in for more intrinsic reasons than were nonspiritual strivings. Investing goals with a sense of sacredness confers on them a power to organize experience and to promote well-being that is absent in nonsacred strivings (Mahoney et al, 1999).…”
Section: Powermentioning
confidence: 99%